Peran Guru dalam Pembentukan Karakter Peserta Didik di SMA Negeri 4 Padang - Sari, Elmia - (Bimbingan dan Konseling, 2014)
This research has point of departure at less optimally studentâs character development in school environment like toward the teachers and their friends. The purpose of estabilishing this research is lescribing teacherâs role toward studentâs character at SMA Negeri 4 Padang, with limitation of the problem is the teacherâs role as effective lovers, model and instructor who have ethic in estabilishing studenâs character. Kinds of research is descriptive qualitative. Populasi is all of students at SMA Negeri 4 Padang. With 853 students. The technique of sampling is stratified random sampling. The total sample is 89 students. Then, the instrument which used question naire. Moreover, to analyze the data, the reseacher use percentage technique. The result of the research show that most of student state teachers have a lot of role toward estabilishing studentâs character. The result of the research based on the sub variable are 1) the teacherâs role as effektive lover, the students say that the teacher have a lot of role in establishing studentâs character, 2) the studentâs perception about teacherâs role as a model also show the same result is the teachers have a lot of role in establishing studentâs character, 3) the studentâs also say that the teacherâs have a lot of role in establishing studentâs character in their role as a instructor. Therefore, studentâs character will be good if teacherâs have more frequent role establishing studentâs character.